Discontinuity of Cardiac Follow‐Up in Young People With Congenital Heart Disease Transitioning to Adulthood: A Systematic Review and Meta‐Analysis - Philip Moons; Sandra Skogby; Ewa‐Lena Bratt; Liesl Zühlke; Ariane Marelli; Eva Goossens (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background The majority of people born with congenital heart disease require lifelong cardiac follow‐up. However, discontinuity of care is a recognized problem and appears to increase around the transition to adulthood. We performed a systematic review and meta‐analysis to estimate the proportion of adolescents and emerging adults with congenital heart disease discontinuing cardiac follow‐up. In pooled data, we investigated regional differences, disparities by disease complexity, and the impact of transition programs on the discontinuity of care. Methods and Results Searches were performed in PubMed, Embase, Cinahl, and Web of Science. We identified 17 studies, which enrolled 6847 patients. A random effects meta‐analysis of single proportions was performed according to the DerSimonian‐Laird method. Moderator effects were computed to explore sources for heterogeneity. Discontinuity proportions ranged from 3.6% to 62.7%, with a pooled estimated proportion of 26.1% (95% CI, 19.2%–34.6%). A trend toward more discontinuity was observed in simple heart defects (33.7%; 95% CI, 15.6%–58.3%), compared with moderate (25.7%; 95% CI, 15.2%–40.1%) or complex congenital heart disease (22.3%; 95% CI, 16.5%–29.4%) (P=0.2372). Studies from the United States (34.0%; 95% CI, 24.3%–45.4%), Canada (25.7%; 95% CI, 17.0%–36.7%), and Europe (6.5%; 95% CI, 5.3%–7.9%) differed significantly (P=0.0004). Transition programs were shown to have the potential to reduce discontinuity of care (12.7%; 95% CI, 2.8%–42.3%) compared with usual care (36.2%; 95% CI, 22.8%–52.2%) (P=0.1119). Conclusions This meta‐analysis showed that there is a high proportion of discontinuity of care in young people with congenital heart disease. The highest discontinuity proportions were observed in studies from the United States and in patients with simple heart defects. It is suggested that transition programs have a protective effect. Registration URL: www.crd.york.ac.uk/prospero. Unique identifier: CRD42020182413.